“Attitude towards Feminism and Homosexuality among Millennials and Post-Millennials Males” - Singh, Soumya; Srivastava, Shweta (International Journal of Psychosocial Rehabilitation, 2020)
Today women are playing a very important role in our society, they expect equality in all opportunities, treatment, respect and social rights, and to achieve this fully they started a movement of feminism. While Homosexuality is being practiced from very beginning in our society but still it is a taboo in our society. Same time it is being observed that the thought process, belief system and attitude of people towards various issues change with the time. Thus, present study aimed at comparing the attitude of millennials and post-millennials on a very major contemporary issue that is feminism and homosexuality. Sample size is 120 males (60 Millennials and 60 Post-Millennials). FEM Scale and Attitude Towards Homosexuality (AHQ) Scale had been administered on the participants. Significant difference had been found on both the variables.